2023
DOI: 10.21062/mft.2023.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Using Cutting Fluid under the Effect of Static Magnetic Field on Chip Formation in Metal Cutting with HSS Tools (turning operation)

Abstract: This paper presents a novel methodology of using cutting fluids to improve the material removal process in metal cutting. To this end, a set of orthogonal cutting experiments are conducted using various cutting fluids to calculate the chip shrinkage coefficient in the material removal process. Chip shrinkage coefficient has been focused on as an important factor that affects chip formation in the material removal process. Using cutting fluids under the influence of a static magnetic field in the metal cutting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The metal-cutting process is a complex of physical and chemical phenomena, which include process kinematics, stress state, plastic deformation, destruction in the cutting zone, friction, thermal phenomena, and chemical, electrical, and magnetic phenomena on contact surfaces [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The metal-cutting process is a complex of physical and chemical phenomena, which include process kinematics, stress state, plastic deformation, destruction in the cutting zone, friction, thermal phenomena, and chemical, electrical, and magnetic phenomena on contact surfaces [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this task, it is important to improve the quality and competitiveness of products using energy-saving technologies based on improving the production processes of plates for metal machining tools made of superhard composite materials based on boron nitride [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In previous works [1,2], it was established that when steels are heated above the point of phase transformation, there are extreme temperatures from which, upon cooling, a structure with maximum defectiveness in the crystalline structure is created. It was found that extreme heating temperatures for tool steels are 1100-1200°C.…”
Section: Introductionmentioning
confidence: 99%